Cav2.1 C‐terminal fragments produced in Xenopus laevis oocytes do not modify the channel expression and functional properties. (7th February 2020) - Ménard, Claudine; Charnet, Pierre; Rousset, Matthieu; Vignes, Michel; Cens, Thierry
Abstract: The sequence and genomic organization of the CACNA1A gene that encodes the Cav2.1 subunit of both P and Q‐type Ca 2+ channels are well conserved in mammals. In human, rat and mouse CACNA1A, the use of an alternative acceptor site at the exon 46–47 boundary results in the expression of a long Cav2.1 splice variant. In transfected cells, the long isoform of human Cav2.1 produces a C‐terminal fragment, but it is not known whether this fragment affects Cav2.1 expression or functional properties. Here, we cloned the long isoform of rat Cav2.1 (Cav2.1(e47)) and identified a novel variant with a shorter C‐terminus (Cav2.1(e47s)) that differs from those previously described in the rat and mouse. When expressed in Xenopus laevis oocytes, Cav2.1(e47) and Cav2.1(e47s) displayed similar functional properties as the short isoform (Cav2.1). We show that Cav2.1 isoforms produced short (CT1) and long (CT1(e47)) C‐terminal fragments that interacted in vivo with the auxiliary Cavβ4a subunit. Overexpression of the C‐terminal fragments did not affect Cav2.1 expression and functional properties. Furthermore, the functional properties of a Cav2.1 mutant without the C‐terminal Cavβ4 binding domain (Cav2.1ΔCT2) were similar to those of Cav2.1 and were not influenced by the co‐expression of the missing fragments (CT2 or CT2(e47)). Our results exclude a functional role of the C‐terminal fragments in Cav2.1 biophysical properties in an expression system widely used to study this channel. Abstract : We cloned the long isoform of the rat Cav2.1 Ca 2+ channel (Cav2.1(e47)) and a novel variant of the C‐terminus (Cav2.1(e47s)). Both variants and the short isoform (Cav2.1) display similar functional properties and produce C‐terminals fragments (α1ACT) in Xenopus laevis oocytes. These fragments interact with auxiliary Cavβ4 subunit in co‐immunoprecipitation assays. However, their overexpression spares Cav2.1 functional properties in Xenopus oocytes.